(untitled) (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2025)
Problems in learning Indonesian, especially in short story writing material at SMK Negeri 1 Kediri show that the low interest and involvement of students is caused by the use of less interesting learning materials. This has an impact on students’ low understanding of the teaching material. One solution to overcome this problem is to develop learning media, namely teaching materials that can attract attention and increase active participation of students. Therefore, this study aims to develop teaching materials for writing short stories for class X students of SMK Negeri 1 Kediri. This study uses the Research and Development (R&D) method which refers to the development model from Sugiyono, which consists of the following stages: identification of potential and problems, data collection, product design, design validation, design revision, initial trial, product revision, usage trial, and final product revision. The instruments used in data collection were validation questionnaires by material experts, media experts, and teachers, as well as student response questionnaires after field trials. Data analysis techniques were carried out descriptively qualitatively and quantitatively. The results of the study showed that the teaching materials for practicing writing short stories received valid assessments from material experts, media experts, and teachers. From the results of the field trial, it was found that students gave positive responses to the teaching materials developed, both in terms of material content, language used, and the appearance of the teaching materials. These teaching materials were also considered practical in their use and effective in improving student understanding. Thus, it can be concluded that the teaching materials for practicing writing short stories developed in this study are suitable for use as interactive and interesting learning media in learning Indonesian, especially in the material for writing short stories